2011
DOI: 10.1166/jnn.2011.3871
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Bound Letrozole Nanoparticles Restore Sensitivity to Letrozole-Resistant Xenograft Tumors in Mice

Abstract: Letrozole is a potent aromatase inhibitor and superior to other defined selective estrogen receptor modulators such as tamoxifen in treating hormone-responsive postmenopausal breast cancer patients. Patients who receive this drug may become insensitive to the effects of estrogen deprivation induced by letrozole. Letrozole has known side effects on bone metabolism due to systemic ablation of estrogen production. The purpose of this study was to examine the therapeutic efficacy of hyaluronic acid-bound letrozole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…82,83 Nair et al developed hyaluronic acid-bound letrozole nanoparticles (HA-Letr-NPs) and showed that the HA-Letr-NPs can restore the sensitivity of tumors to letrozole in the LTLT-Ca letrozole-resistant breast tumor model. 84 Cho et al developed tamoxifen-incorporated manganese superoxide dismutase (MnSOD) siRNA nanoparticles that have an siRNA/poly(amidoamine) dendriplex core and an acid-sensitive polyketal shell and showed that the tamoxifen resistance of breast cancer cells was reversed when the antagonistic MnSOD activity was silenced by the MnSOD siRNA nanoparticles both in vitro and in vivo. 85 …”
Section: Hormones and Hormone Antagonistsmentioning
confidence: 99%
“…82,83 Nair et al developed hyaluronic acid-bound letrozole nanoparticles (HA-Letr-NPs) and showed that the HA-Letr-NPs can restore the sensitivity of tumors to letrozole in the LTLT-Ca letrozole-resistant breast tumor model. 84 Cho et al developed tamoxifen-incorporated manganese superoxide dismutase (MnSOD) siRNA nanoparticles that have an siRNA/poly(amidoamine) dendriplex core and an acid-sensitive polyketal shell and showed that the tamoxifen resistance of breast cancer cells was reversed when the antagonistic MnSOD activity was silenced by the MnSOD siRNA nanoparticles both in vitro and in vivo. 85 …”
Section: Hormones and Hormone Antagonistsmentioning
confidence: 99%
“…Briefly, 5 Â 10 3 cells were seeded in 96-well plates and incubated with gossypin (1-200 mmol/L) or dimethyl sulfoxide (DMSO; 0.02% v/v) for 24, 48, and 72 hours at 37 C and cell viability was measured using a Fluoroscan plate reader (Thermo; ref. 24).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…PG-DO3A-Gd-Mce 6 conjugated with PEG reduced nonspecific liver uptake to improve its efficacy as contrast enhanced MRI-guided photodynamic therapy. These agents can efficiently perceive changes in the tissue distribution of polymer conjugates and geode site directed irradiation of target tissues [43].…”
Section: Journal Ofmentioning
confidence: 99%
“…PG-DO3A-Gd-Mce 6 conjugated with PEG reduced nonspecific liver uptake to improve its efficacy as contrast enhanced MRI-guided photodynamic therapy. These agents can efficiently perceive changes in the tissue distribution of polymer conjugates and geode site directed irradiation of target tissues [43].Other polymers including poly L-lysine, N-(2 hydroxypropyl) methylacrilamide (HPMA), and poly (ethylene) oxide were demonstrated for MRI, optical, nuclear, and multimodality imaging applications. Our laboratory showed for the first time that poly lactic co-glycolicacid (PLGA) nanoparticles conjugated with hyaluronic acid increased the therapeutic benefit and enhanced optical imaging properties [44].…”
mentioning
confidence: 99%